Pengaruh Parameter Fisika Terhadap Hasil Tangkapan Alat Tangkap Gill Net Di Perairan Kelurahan Sumber Jaya Kecamatan Kampung Melayu Kota Bengkulu Provinsi Bengkulu - Qadhafi, Muammar; Sari, T. Ersti Yulika; ', Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was done in December 2013 in the waters of Sumber Jaya village Kampung Melayu subdistrict Bengkulu Bengkulu province. The method used was a survey method. Data taken consisted of 1) the location of the operation of gill net fishing gear, 2) the location of the catch in gill net fishing gear pengoperaisan, 3) water temperature, 4) salinity, 5) flow velocity, 6) brightness and 7) depth. The highest fish production in the 10 operating locations gill net fishing gear different, for gill net boats GT ≤ 5 highest and lowest 110 kg 45 kg. While gill net vessel GT ≥ 5 highest and lowest reaches 750 kg 350 kg. Physical parameters obtained for salinity in the range of 24-26 ‰, flow velocity in the range of 0.200 to 0.250 m / sec, the depth was 58-62 m range, water transparency in the range of 6.0-8.0 m, water temperature in the range of 27 -30 0C. Multiple linear regression analysis showed Total catches (Dependent Variable) with physical parameters (Predictors) obtained the effect of x on y by 54.0%, while the remaining 46% are caused by other factors. The need for further research by grouping objects larger research and predictive variables that have continuous time series in order to obtain a clearer influence between variables and objects.Keywords: water village Sumber Jaya, gill net, physical parameters, multiple linear regression